Coated Urea Materials for Improving Yields, Profitability, and Nutrient Use Efficiencies of Aromatic Rice. Issue 12 (5th September 2019) - Shivay, Yashbir Singh; Pooniya, Vijay; Pal, Madan; Ghasal, Prakash Chand; Bana, Ramswaroop; Jat, Shankar Lal
Abstract: Intensive cultivation and introduction of input‐responsive high‐yielding varieties with application of major nutrients in rice–wheat rotation of Indo‐Gangetic plains (IGPs) lead to multiple nutrient deficiencies. A survey of Indian soils has shown that 40% are deficient in available zinc (Zn), 33% in sulfur (S), and 33% in boron (B). Studies have indicated that application of these nutrients with major nutrients can improve the crop productivity. Keeping the importance of aromatic rice in view, coated‐urea materials and their effects on rice yields, nitrogen (N), and Zn content in different parts and input economics are evaluated. Three field trials are conducted on aromatic rice to test boron‐coated urea (BCU), sulfur‐coated urea (SCU), and zinc‐coated urea (ZnCU) in 2013 and 2014. Results indicate that the highest yields are obtained with 0.5% BCU, 5.0% SCU, and 2.5% ZnCU as zinc sulfate heptahydrate. These treatments increase grain yield by 13%, 25%, and 17.9% over prilled urea (PU). Moreover, 0.5% BCU, 5% SCU, and 2.5% ZnCU register the highest N, S, and Zn contents in bran, husk, grain, and straw. Coated‐urea materials also improve use efficiencies and harvest index of N and Zn over PU. The findings of this study suggest that 0.5% boron, 5.0% sulfur, or 2.5% zinc‐coated urea show improvement in returns and benefit–cost ratio in aromatic rice of western IGPs. Abstract : Micro–(Zn, B) and secondary (S) nutrients coating onto prilled urea leads to maximized benefits and increased N/Zn–use efficiencies.